Effects of bradykinin on proliferation, apoptosis, and cycle of glomerular mesangial cells via the TGF-β1/Smad signaling pathway - DONG, Ji (Turk J Biol, 2021)
We aimed to assess the effects of bradykinin (BK) on the proliferation, apoptosis, and cycle of glomerular mesangial cells via the transforming growth factor-β 1 (TGF-β1)/Smad signaling pathway. Rat glomerular mesangial cells, HBZY-1, were divided into normal group (untreated), model group (5 ng/L TGF-β1), BK group (5 ng/L TGF-β1 + 1 ng/L BK), and inhibitor group [5 ng/L TGF-β1 + 1 ng/L LY2109761 (TGF-β1-specific inhibitor)]. The cell proliferation, cycle, apoptosis, expression of type I collagen (Col-1), and protein expressions of Col-1, TGF-β1, and phosphorylated Smad2 (p-Smad2) were detected by EdU labeling, flow cytometry, acridine orange/ethidium bromide (AO/EB) dual staining, immunofluorescence assay, and Western blotting, respectively. Compared with the normal group, the cell proliferation rate (P = 0.02) and protein expression levels of Col-1 (P = 0.02), TGF-β1 (P = 0.01), p-Smad2 (P = 0.02), and p-Smad7 (P = 0.00) in the model group significantly increased, and apoptosis rate (P = 0.01) significantly decreased. Compared with the model group, the BK and inhibitor groups significantly decreased in proliferation rate (P = 0.01) and protein expression levels of Col-1 (P = 0.01), TGF-β1 (P = 0.01), and p-Smad2 (P = 0.00). Also, they were significantly elevated in apoptosis rate (P = 0.02) and p-Smad7 protein expression (P = 0.02). BK regulates the proliferation, apoptosis, and the cycle of glomerular mesangial cells by inhibiting the TGF-β1/Smad signaling pathway.